1996
DOI: 10.1111/j.1346-8138.1996.tb02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Pruritic Papular Eruptions and Candidiasis Due to HIV Infection

Abstract: We present two patients with refractory papular eruptions and severe candidiasis. Both of them are positive for treponema pallidum and have suffered from pruritic papular eruptions (PPE) that had resisted therapy for years. Also, candidiasis appeared in the mouth, at intertriginous sites, and on the feet. The clinical features suggested immunodeficiency, and HIV tests were positive. Histologically, the specimen from the PPE lesion showed perivascular and perifollicular mixed cell infiltration. The fungus was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…As suggested by many authors (8,15,19), these two diseases seem to lie within the same histologic and clinical spectrum. The chronic persistent eruption on the trunk in our patient, manifesting multiple, excoriated, prurigolike nodules, was typical of that in reported cases of pruritic papular eruption (18,20), which is considered to be a chronic and long-standing eruption of HIV-associated eosinophilic pustular folliculitis. However, another type of "papular eruption" reported to occur in patients with HIV infection, which shows the histologic features of dermal fibrosis or granuloma (21,22), should be considered as a completely different clinicalentity (19).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As suggested by many authors (8,15,19), these two diseases seem to lie within the same histologic and clinical spectrum. The chronic persistent eruption on the trunk in our patient, manifesting multiple, excoriated, prurigolike nodules, was typical of that in reported cases of pruritic papular eruption (18,20), which is considered to be a chronic and long-standing eruption of HIV-associated eosinophilic pustular folliculitis. However, another type of "papular eruption" reported to occur in patients with HIV infection, which shows the histologic features of dermal fibrosis or granuloma (21,22), should be considered as a completely different clinicalentity (19).…”
Section: Discussionsupporting
confidence: 82%
“…Cases of HIV infection, an entity showing similar clinicopathological features to the HIV-associated form, were also reported under the term pruritic papular eruption (15). A few Japanese cases of pruritic papular eruption associated with HIV infection have been reported (16)(17)(18). As suggested by many authors (8,15,19), these two diseases seem to lie within the same histologic and clinical spectrum.…”
Section: Discussionmentioning
confidence: 91%
“…Some of the research showed that the presence of papular eruptions predicts the advanced disease of HIV infection. A former study also revealed that this problem correlates with considerable morbidity .ling and is poorly responsive to conventional therapy (21)(22)(23)(24)(25).…”
Section: Papular Eruptionmentioning
confidence: 99%
“…A former study also revealed that this problem causes considerable morbidity and is poorly responsive to conventional therapy. [21][22][23][24][25]…”
Section: Nodular Prurigo (Papular Pruritic Eruption)mentioning
confidence: 99%